A survey to describe current feeder calf health and well-being program recommendations made by feedlot veterinary consultants in the United States and Canada - Terrell, Shane Patrick (Kansas State University, 2012)
Consulting veterinarians (CV; n=23) representing 11,295,000 head of cattle on feed in the United States and Canada participated in a beef cattle health and well-being recommendation survey. Veterinarians were directed to an online survey to answer feeder cattle husbandry, health and preventative medicine recommendation questions. The CV visited their feedyards 1.7 times per month. All CV train employees on cattle handling and pen riding while only 13% of CV speak Spanish. All CV recommend IBR and BVD vaccination for high-risk (HR) calves at processing. Other vaccines were not recommended as frequently by CV. Autogenous bacterins were recommended by 39.1% CV for HR cattle. Metaphylaxis and feed-grade antibiotics were recommended by 95% and 52% of CV, respectively, for HR calves. Banding was more frequently recommended than surgical castration as calf body weight increased. The CV recommended starting HR calves in smaller pens (103 hd/pen) and allowing 13 inches/hd of bunk space. The CV indicated feedlots need to employ one feedlot doctor per 7,083 hd of HR calves and one pen rider per 2,739 hd of HR calves. Ancillary therapy for treating respiratory disease was recommended by 47.8% of CV. Vitamin C was recommended (30.4%) twice as often as any other ancillary therapy. Cattle health risk on arrival, weather patterns and labor availability were most important factors in predicting feedlot morbidity while metaphylactic antibiotic, therapy antibiotic and brand of vaccine were least important. This survey has provided valuable insight into feeder cattle health recommendations by CV and points to needed research areas.
Keywords: Feedlot; Feeder calf health; Recommendations by feedlot veterinary consultants; Veterinary Medicine (0778)